PERSEPSI MASYARAKAT TERHADAP NILAI-NILAI NAZAM ACEH DI KECAMATAN PIDIE - Fajri, Heri; Nadia, Adrami; Zaini, Muhammad (Jurnal Sosial Humaniora Sigli, 2024)
Nazam is one of the elements of classical Acehnese culture and is full of local wisdom that contains values in it and needs to be preserved so that it is not eroded by the development of the times. This study aims to (1) analyze the development of Acehnese nazam in Pidie sub-district (2) analyze the characteristics of Acehnese nazam in Pidie sub-district, (3) analyze the perception of Pidie sub-district society about the values of Acehnese nazam in Pidie sub-district. The research method uses a qualitative research method with a descriptive approach. Data collection techniques used are observation, interviews, literature studies and documentation. The results of this study indicate that (1) the development of Acehnese nazam in Dayah Teubeng village, Pidie sub-district has developed since 1960, at that time nazam readers were very popular, nazam literature was presented in the form of the meudike tradition. In 1990, a youth leader at the Abdullah Sa'ad mosque copied and reproduced the Nazam text and compiled it into a book, The development of Aceh's Nazam in the 2000s among Islamic students, especially those studying religion at the Yata'allamu study hall. Children and teenagers are required to be able to memorize the Nazam in both Arabic and Javanese. The development of Aceh's nazam is now starting to decline, many generation Z are not familiar with nazam (2) Nazam which is very popular in Dayah Teubeng village, Pidie sub-district consists of three nazams, namely nazam lam yahtalim, nazam tauhid, and nazam advice on life. This nazam has its own characteristics and is known by all levels of the Dayah Teubeng village community. (3) Community perception of the values of nazam, namely the values contained are religious values, educational values and cultural values. The perception of the Dayah Teubeng village community varies depending on which perspective they judge it from. Keywords: Nazam, perception, values, community